Katya & the prince of Siam - Hunter, Eileen; Narisa Chakrabongse, M. R. (Bangkok : River Books, 1994)
Biography of Phitsanulokprachanat, Prince, son of Chulalongkorn, King of Siam, 1882-1920, and his wife, Ekaterina Ivanovna Desnitsky, 1888-1960
Includes bibliographical references (p. 212) and index
Keywords: Phitsanulokprachanat, -- Prince, son of Chulalongkorn, King of Siam, -- 1882-1920; Desnitsky, Ekaterina Ivanovna, -- 1888-1960; Princes -- Thailand -- Biography; Wives -- Thailand -- Biography